Transformasi Digital Koperasi melalui Localoka BRI: Analisis Social Return on Investment (SROI) pada Koperasi FEB Universitas Airlangga - Darliyanti, Novita Ika; Nurbuati, Dyah; Julinda Ekawati, Renitha (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The digital transformation of cooperatives has become a crucial strategy to enhance competitiveness and ensure sustainable member-based enterprises. This study aims to analyze the Social Return on Investment (SROI) of the program Future Finance: Transforming FEB Unair Cooperative into Digital Transactions with BRI through the utilization of the Localoka platform. The research employed the SROI framework, which includes stakeholder identification, impact mapping, outcome monetization, and SROI ratio calculation. Data were collected through event observation, documentation, and program financial reports. The findings reveal that the program generated outcomes worth IDR 1,050,025,000 with an input of IDR 52,381,000, resulting in an SROI ratio of 20.05. This indicates that every IDR 1 invested in the program yields a socio-economic return of IDR 20.05. The results highlight that the collaboration between the cooperative and BRI through Localoka not only fosters digital transaction adoption but also contributes positively to digital literacy, institutional reputation, and the economic welfare of cooperative members. This study provides practical implications for developing cooperative–financial institution partnerships to strengthen the digital ecosystem of MSMEs in Indonesia.